Initial oxidation processes of ultrathin hafnium film and hafnium disilicide islands on Si(100)-2 × 1 surfaces studied using core-level X-ray photoelectron spectroscopy - Kakiuchi, Takuhiro; Yamasaki, Hideki; Tsukada, Chie; Yoshigoe, Akitaka (Surface science, 2020)
•Chemical states of clean ultrathin hafnium film on Si(100) were analyzed by core-level photoelectron spectroscopy.•Initial oxidation of clean ultrathin hafnium film on Si(100) was investigated by core-level photoelectron spectroscopy.•Metallic hafnium on Si(100) rapidly oxidized, while silicides at interface did not.•After annealing over 1073 K, oxygen atoms were entirely removed from the ultrathin hafnium dioxide.•Dangling bonds on Si(100)-2 × 1 surface with residual hafnium atoms preferentially oxidized because back-bonds of the Si dimers were occupied by hafnium. We investigated the initial oxidation of ultrathin hafnium (Hf) film on Si(100)-2 × 1 [Hf/Si(100)] using high resolution Hf 4f5/2, 7/2, Si 2p1/2, 3/2, and O 1s core-level photoelectron spectroscopy. Ultrathin Hf/Si(100) film was prepared using electron-beam evaporation in an ultrahigh vacuum chamber below 1.5 × 10−8 Pa. Our results revealed the formation of metallic Hf layers containing a few Si atoms on the Si(100)-2 × 1 substrate. A Hf monosilicide (HfSi) component was also formed in the vicinity of the interface region. Metallic Hf rapidly oxidized, transforming into hafnium dioxide (HfO2) and its suboxides, after exposure to O2 molecules at <4.1 Langmuir. In accordance with the oxidation of metallic Hf, Si atoms in metallic Hf layers were also oxidized into typical Si (sub)oxides and Hf silicate. The other HfSi component at the interface was nearly unreactive with O2 molecules. These facts suggest that the metallic Hf component plays a vital role in the initial oxidation of the ultrathin Hf/Si(100) film. After annealing from 873 K to 973 K, the Hf suboxides in low ionic valences progressed into fully oxidized HfO2. Once the annealing temperature reached ~1073 K, oxygen atoms were entirely removed from the ultrathin HfO2/Si(100) film containing SiO2 at the interface. Simultaneously, ultrathin HfO2 layers changed into islands of Hf disilicide (i-HfSi2) on a bare Si(100)-2 × 1 surface. The i-HfSi2 component showed slight reactivity with O2 molecules at 298 K. In contrast to the initial oxidation of clean Si(100)-2 × 1 surface, the dangling bonds on bare Si(100)-2 × 1 surface among i-HfSi2 oxidized preferentially. This was due to some back-bonds of the Si dimers on bare Si(100)-2 × 1 that were occupied by Hf atoms in the form of HfSi2. [Display omitted]